A bioinspired strategy towards super-adsorbent hydrogel spheres via self-sacrificing micro-reactors for robust wastewater remediation. Issue 37 (9th September 2019) - Song, Xin; An, Jiangle; He, Chao; Zhou, Jukai; Xu, Yuanting; Ji, Haifeng; Yang, Li; Yin, Jiarui; Zhao, Weifeng; Zhao, Changsheng
Abstract : A bioinspired strategy via self-sacrificing micro-reactors is proposed to prepare hydrogel spheres with ultrahigh adsorption capability within 150 seconds. Abstract : Super adsorbents with ultrahigh adsorption capabilities are highly desired for efficient wastewater remediation. However, most of the adsorbents with high adsorption capabilities are powdery adsorbents, showing inescapable limitations in practical adsorption column application. It is practically urgent to develop a simple and effective method for preparing adsorbents with ultrahigh adsorption capability and convenient column operation ability. Herein, inspired by oviparity, we fabricate super-adsorbent hydrogel spheres (SAHSs) based on self-sacrificing micro-reactors, which achieve the interior cross-linking polymerization of the hydrogel network and subsequent self-disintegration within only 150 seconds. The as-prepared poly(2-acrylamido-2-methyl-propanesulfonic acid- co -acrylic acid) hydrogel spheres show outstanding adsorption capabilities toward organic dyes (4625 ± 231 mg g −1 for methylene blue) and heavy metallic ions (4312 ± 185 mg g −1 for Pb(ii )). Remarkably, the adsorption column packed with the SAHSs exhibits splendid removal abilities for organic dyes, which can purify 6280 mL of dye-containing wastewater (150 μmol L −1 ) thoroughly using only 7 mL SAHSs. This is the first time that a maximum dynamic removal capacity over 50 g L −1 spheres has been obtained using an adsorption column. In addition, the hydrogel spheres also show good recyclability, dynamic filtration–regeneration, selective adsorption and smart separation–regeneration. Thus, the oviparity-inspired method to fabricate super-adsorbent hydrogel spheres has great potential to be used in efficient, economical and environmental wastewater treatment.